Flexural Strength Characteristics of Fiber-Reinforced Cemented Soil - Pedroso, Gabriel Orquizas Mattielo [UNESP]; dos Santos Junior, Ricardo Domingos; Lins da Silva, Jefferson; Motta, Mariana Ferreira Benessiuti [UNESP]; Félix, Emerson Felipe [UNESP] (MDPI, 2023)
This work deals with the flexural performance of a soil-cement for pavement reinforced by polypropylene and steel fibers, and the main purpose is to evaluate the effect of different curing times. In this sense, three different curing times were employed to investigate the influence of fibers on the material’s behavior at varying levels of strength and stiffness as the matrix became increasingly rigid. An experimental program was developed to analyze the effects of incorporating different fibers in a cemented matrix for pavement applications. Polypropylene and steel fibers were used at 0.5/1.0/1.5% fractions by volume for three different curing times (3/7/28 days) to assess the fiber effect in the cemented soil (CS) matrices throughout time. An evaluation of the material performance was carried out using the 4-Point Flexural Test. The results show that steel fibers with 1.0% content improved by approximately 20% in terms of initial strength and peak strength at small deflections without interfering the flexural static modulus of the material. The polypropylene fiber mixtures had better performance in terms of ductility index reaching values varying from 50 to 120, an increase of approximately 40% in residual strength, and improved cracking control at large deflections. The current study shows that fibers significantly affect the mechanical performance of CSF. Thus, the overall performance presented in this study is useful for selecting the most suitable fiber type corresponding to the different mechanisms as a function of curing time.
Keywords: cemented soil; flexural performance; pavement; polypropylene fibers; steel fibers